EKSTRAK METANOL DAUN KERSEN (Muntingia calabura L) SEBAGAI ANTIMIKROBA ALAMI TERHADAP BAKTERI Staphylococcus aureus PENYEBAB MASTITIS SUBKLINIS PADA SAPI PERAH - Happy Aprilia Mahardika; Sarwiyono Sarwiyono; Puguh Surjowardojo (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2014)
This research was conducted in the laboratory of Bacteriology, Faculty of Agriculture, University of Brawijaya Malang. The purpose of this study is to determine the effect of cherry leaf methanol extract on the growth of Staphylococcus aureus bacteria causing subclinical mastitis in dairy cows. Materials used in this research were Staphylococcus aureus, cherry leaf methanol extract, cherry leaf water extract and iodips. The method used in this research is experiment with a completely randomized design (CRD) with 6 treatments and 4 replications. The results showed that the cherry leaf methanol extract, with a concentration of 10%, 20%, 30% and 40% have an influence on the growth inhibitory Staphylococcus aureus. Cherry leaf methanol extract has no significant difference (P> 0.05) with a cherry leaf water extract and iodips as antimicrobial substances, so it can be used as a natural antimicrobial substance to inhibit the growth of Staphylococcus aureus bacteria causing subclinical mastitis. Key word : cherry leaf, methanol extract, Staphylococcus aureus and mastitis